Package for fiber Bragg gratings (FBG) and a comparative study on their polarization mode dispersion (PMD) at varying temperature - Ning, Tigang; Pei, Li; Liu, Yan; Tan, Zhongwei; Wang, Qi; Zheng, Jingjing; Jian, Shuisheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A temperature-compensated material of fiber Bragg grating (FBG), which has negative thermal-expansion coefficient has been presented. The temperature coefficient of FBGs’ center wavelength is less than 0.0005 nm/°C after three-layer-structure temperature-compensated package under tension. For the first time, PMD of FBG with and without temperature compensation has been detailedly studied and measured from –20 to 60°C. The measured result shows that the PMD changes a little at varying temperature, which means that the package did not affect the PMD characteristic of FBG.
Optica Applicata, Vol. 35, 2005, nr 2, s. 277-282
Keywords: optyka; optical fiber communication; fiber Bragg grating; negative thermal-expansion material; temperature-compensated package; PMD